On the growth of derivatives of algebraic polynomials in a weighted Lebesgue space - Аbdullayev, F. G.; Imashkyzy, M.; Аbdullayev, Fahreddin; Аbdullayev, F. G.; Imashkyzy, М. (Institute of Mathematics, NAS of Ukraine, 2022)
UDC 517.5 We study growth rates of derivatives of an arbitrary algebraic polynomial in bounded and inbounded regions of the complex plane in weighted Lebesgue spaces.